A novel discharge pathway for patients with advanced cancer requiring home parenteral nutrition. Issue 4 (21st April 2019) - Bond, A.; Teubner, A.; Taylor, M.; Willbraham, L.; Gillespie, L.; Farrer, K.; McMahon, M.; Leahy, G.; Abraham, A.; Soop, M.; Clamp, A. R.; Hasan, J.; et al.
Abstract: Background: The use of home parenteral nutrition (HPN) for palliative indications is increasing internationally and is the leading indication in some countries. Discharge on HPN can be complex in metabolically unstable patients and requires intestinal failure expertise. Methods: Between 2012 and 2018, we performed a retrospective analysis aiming to assess the impact of a novel remote discharge pathway for palliative HPN patients. This was evaluated using a quality improvement approach. Results: One hundred and twenty‐five patients with active malignancy [mean (range) age 58 (25–80) years] were referred to the intestinal failure unit (IFU) for remote discharge. Of 82 patients were discharged from the oncology Centre on HPN using the pathway. The remaining 43 patients either declined HPN or the Oncology team felt that the patient became too unwell for HPN or died prior to discharge. There was an increase in patients referred for remote discharge from 13 in 2012 to 43 in 2017. The mean number of days between receipt of referral by the IFU to discharge on HPN from the oncology centre reduced from 29.4 days to 10.1 days. Following remote discharge, the mean number of days on HPN was 215.9 days. Catheter‐related blood stream infection rates in this cohort were very low at 0.169 per 1000 catheter days. Conclusions: This is the first study to demonstrate the remote safe, effective and rapid discharge of patients requiring palliative HPN between two hospital sites. This allows patients with a short prognosis more time in their desired location.